Clifford Simak: from "Pastoral Science Fiction" to a Metagenre. - Паранюк, Дан (Чернівецький нац. Ун-т, 2025)
The article presents an attempt of a comprehensive analysis of Clifford Simak’s creative activities as one of the most prominent representatives of the American XX century science fiction. The objective of this study is to outline the genealogical specifics of C. Simak’s works, to trace up their evolution from the «pure» science fiction to the metagenre of fantasy, and to identify the key factors that had the greatest impact on the formation of the author’s style. The article systematizes the basic stages of C. Simak’s literary evolution, shows the transformation of motives, chronotope, and personosphere, as well as reveals the writer’s significance as an innovator who managed to combine science fiction with fantasy and metaphysical components. The outcomes of the study make it possible to determine C. Simak’s place in the history of world science fiction and justify his role as a «pastoral humaniat» that has broadened the boundaries of a metagenre.
Keywords: Clifford Simak, science fiction, fantasy, biography, author